Corporate governance and cost of capital: Evidence from emerging market - Muhammad Yar Khan; Anam Javeed; Ly Kim Cuong; Pham Ha (Risks, 2020)
This study used a researcher self-constructed corporate governance index as a proxy to measure the firm-level corporate governance compliance and disclosure with the 2002 Pakistani Code of Corporate Governance, to examine the relationship between corporate governance and cost of capital. We found a negative and significant association between the Pakistani Corporate Governance Index (PCGI) and block ownership with the firm-level cost of capital. On average, better-governed Pakistani listed firms tend to be associated with a lower cost of capital than their poorly governed counterparts are. As an emerging market, good corporate governance practices are mainly related to minimise corporate failure and assist firms in attracting capital at a lower cost.
Keywords: 330; grouped normal variance mixtures; distribution functions; densities; copulas; grouped t copula; risk measures; quasi-random number sequences